Studi Dekonstruksi: Menyingkap Identitas Muslimah Di Media Rahma.id - Mawlana, Akbar; Ulumuddin, Naufalul Ihya; Pratama, Adhitya Prasta (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2022)
Women in Islam are subjects who often experience recognition instability. Instability is formed through universality logocentrism that has been established in people's consciousness. People's judgments always focus